Ethnography by design scenographic experiments in fieldwork - Cantarella, Luke; Hegel, Christine; Marcus, George E. (Bloomsbury Academic, 2019)
Ethnography by Design, unlike many investigations into how ethnography can be done, focuses on the benefits of sustained collaboration across projects to ethnographic enquiry, and the possibilities of experimental co-design as part of field research.